FROM THERE TO HERE: USING PHOTOGRAPHY TO EXPLORE PERSPECTIVES OF RESETTLED REFUGEE YOUTH - Jody Lynn McBrien; Rebecca Day (International Journal of Child, Youth & Family Studies, 2012)
Because refugee numbers are much smaller than those of other immigrant populations in the United States, researchers frequently group refugees with other immigrants in their studies. However, due to the traumatic circumstances that most refugees face prior to their arrival, they require separate consideration. We chose the medium of photography to help newcomer refugee students express themselves beyond their current capacities in English, and we used the students’ photographs as catalysts to interview them about their resettled lives in the United States. Through this process, we discovered themes central to the students’ lives, and ways in which they were working to reconcile important past and present elements, such as family, friends, cultures, and aspirations. Bronfenbrenner’s (1986) ecological theory provides a useful frame for exploring these students’ processes of acculturation. Their photos, and their commentaries, provide critically important information for teachers, social service providers, and others working with refugee youth.